Desmosomal plakophilin 2 as a differentiation marker in normal and malignant tissues - Mertens, Claudia; Franke, Werner (Differentiation, 2009)
Plakophilin 2 (PKP2) is a widespread protein which shows a remarkable dual location: On the one hand, it appears as a constitutive karyoplasmic protein and on the other it is a desmosomal plaque component of most, probably all, desmosome-possessing tissues and cell culture lines. Here we report on its desmosomal occurrence as revealed by immunocytochemical results obtained with three PKP2-specific murine monoclonal antibodies (mAbs) PP2-62, PP2-86 and PP2-150. These mAbs detect PKP2 in characteristic desmosomes of most normal cells, including simple and stratified epithelia as well as non-epithelial tissues such as myocardium and lymph node follicles. In addition, however, several normal tissues consistently display a differentiation-related PKP2 distribution, for example an absence of immunostaining in the “keratinizing” local specializations of the thymic epithelial reticulum, i. e. Hassall's corpuscles, and the restriction of PKP2 to the stratum basale of most stratified squamous epithelia, in contrast to its absence in upper strata, which contain PKP1- or PKP3-rich desmosomes instead. Taking advantage of the reactivity of mAb PP2-150 with formalin-fixed, paraffin-embedded material, a series of human carcinomas (n=37) has also been analyzed. The results suggest that mAbs to PKP2 may serve as markers for the identification and characterization of carcinomas derived from - or corresponding to - simple or complex epithelia. Thus consistent PKP2 immunostaining has been observed in all 18 cases of adenocarcinomas tested, but more variable and heterogeneous staining has been noted in squamous cell carcinomas, depending on the specific tumor type. The potential value of such mAbs for cell typing in normal and embryonic tissues and for detecting cell subpopulations with different degrees of differentiation is discussed with respect to their possible application in tumor diagnosis.
Available online 30 November 2009
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 11.02.2021